2008
DOI: 10.1097/ana.0b013e3181778156
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Pulmonary Edema in Patients With Subarachnoid Hemorrhage

Abstract: Neurogenic pulmonary edema (NPE), leading to cardiopulmonary dysfunction, is a potentially life-threatening complication in patients with aneurysmal subarachnoid hemorrhage (SAH). We sought to assess the clinical presentation and risk factors for the development of NPE after SAH. The database contained prospectively collected information on 477 patients with SAH. Baseline characteristics, clinical and radiologic severity of the bleeding, localization of the ruptured aneurysm, and clinical outcome of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 21 publications
4
85
3
2
Order By: Relevance
“…6,7) These findings may explain why poor-grade patients with ruptured posterior circulation aneurysm were significantly more likely to sustain NPE compared with anterior circulation aneurysm, as previously reported. 25,26) The results of this study, shown in Fig. 1B and Table 2, are compatible with the previous findings.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…6,7) These findings may explain why poor-grade patients with ruptured posterior circulation aneurysm were significantly more likely to sustain NPE compared with anterior circulation aneurysm, as previously reported. 25,26) The results of this study, shown in Fig. 1B and Table 2, are compatible with the previous findings.…”
supporting
confidence: 93%
“…Ruptured posterior circulation aneurysms may also cause NPE more frequently compared with anterior circulation aneurysms. 25,26) In our institution, transthoracic ultrasonography is performed routinely in the emergency department for SAH patients presenting with the clinical/radiographic signs of NPE, allowing investigation of the incidence and demographics of SAH patients complicated with NPE-TCM.…”
Section: J Inamasu Et Almentioning
confidence: 99%
See 3 more Smart Citations